Mechanical evaluation of nano hydroxyapatite, chitosan and collagen composite coating compared with nano hydroxyapatite coating on commercially pure titanium dental implant - Ibrahim, Sabreen W; Al Nakkash, Widad A (Journal of Baghdad College of Dentistry, 2017)
Background: Dental implants act as infrastructure for fixed restoration to look like as a natural tooth. Osseointegration is a biological events and considered as a base for success of dental implant. The aim of this study is to evaluate the bond strength between bone and Ti implant coated with mixture of nano hydroxyapatite-chitosan-collagen compared with Ti implants coated with nano hydroxyapatite implanted in rabbit tibia, after different period of implantation time (two and six weeks) by torque removal test.Material and methods: 36 screws of commercially pure titanium; 8mm in length and 3mm diameter , 18 screws coated with mixture of nano hydroxyapatite-chitosan-collagen and18 screws coated with nano hydroxyapatite by dip coating. Structural characteristics was assessed by scanning electron microscope, and FTIR analysis. The screws were implanted in 18 healthy adult male New Zeeland rabbits each tibia received one screw, right tibia received screw coated with nano hydroxyapatite while left tibia received screw coated nano hydroxyapatite-chitosan-collagen composite. Removal torque test was done by torque meter to determine the highest torque value necessary to remove the implants from tibia bone after different period of time of implantation(2 and 6 weeks). Result: Nano hydroxyapatite-chitosan-collagen composite coating was resulting in higher torque removal value than nano hydroxyapatite coating for two periods of time. Conclusion: Concluded that addition of collagen and chitosan to nano hydroxyapatite was more efficient in rapid bone formation than nano hydroxyapatite only.